Relationships Between Work, Family and Individual Factors with Work-Family Conflict Among Nurses in Shiraz, Iran - Namayandeh, Hajar (2010)
The aim of this study was to determine the relationships between work, family, and individual factors with work-family conflict among married female nurses in public hospital in Shiraz-Iran. This study employed a quantitative approach and correlational design. Respondents of the study were selected randomly from 13 public hospitals in Shiraz. The self-administered questionnaires were distributed to 323 married female nurses and only 198 (61.30%) questionnaires were returned. The questionnaire taps information on respondents’ demographic background (age, duration of marriage, job experience, number of the children), work factors (job demand, job satisfaction, and workplace social support: support from supervisor and co-worker), family factors (fairness of division in family responsibility, family satisfaction and family social support: support from husband and family members/relatives) and individual factor (gender role orientation) and work-family conflict. The Pearson correlation analysis was conducted to determine the magnitude and direction of relationships between the independent variables and dependent variable. Multiple Regression analysis was conducted to determine predictors of work-family conflict. Results of the Pearson correlation analysis showed that work-family conflict among married female nurses is related to age, job experience, duration of marriage, work factors (job demand, job satisfaction, supervisor support), family factors (family satisfaction, fairness of division in family responsibility, husband support, family members/relatives support) and individual factor (gender role attitude). All independent variables that were significantly correlated with work-family conflict were regressed against W-FC. Based on the Multiple Regression analysis, age, job experience, duration of marriage, job demand, job satisfaction, supervisor support, family satisfaction, fairness of division in family responsibility, husband support, family members/relatives support and gender role attitude in combination contributed about 20.6% of the variance in perceived work-family conflict. The result of multiple regression analysis showed that job demand (β= .244, p <.01) is the only work factor that has significant contribution to W-FC. For family factors, family satisfaction (β= -.142, p <.05) emerged as the only significant contributor of W-FC. Gender role orientations which represents individual factor dose not predict W-FC. Job demand emerged as the strangest predictor of W-FC, follows by family satisfaction. The findings of this study implied the need for relevant policies and programs that could help married female nurses to reduce job demand, increase family satisfaction and finally balance their work and family responsibilities.